Malaria prevention and treatment - A. Jamieson (South African Family Practice)
Family practitioners play an important role in educating patients about the prevention of malaria. Many patients still believe that malaria prophylaxis is negotiable and it is the family practitioner's duty to fully inform patients about the deadly complications of malaria and the rationale behind chemoprophylaxis. This article is patient orientated and will provide the family practitioner with useful information for this important task.